HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPATUHAN PASIEN HEMODIALISA TERHADAP TERAPI GAGAL GINJAL DI RSUD BLAMBANGAN BANYUWANGI - Diyan Ajeng, Dessy (AKADEMI FARMASI JEMBER, 2016)
Chronic Renal Failure (CRF) is a chronic disorder of renal function is progressive and irreversible. In which the body fails to maintain metabolic and fluid and electrolyte balance, causing uremia and could eventually cause a disruption in the body's immune system. According Raharjo (1996) and Lopez (2006), the estimated number of patients with chronic renal failure continues to increase and the estimated growth of about 10% every year.This research design was a descriptive cross sectional study. Have done a study of 55 patients with chronic renal failure who had been treated at the Hospital Medicine at Blambangan, Banyuwangi in 2014 patient data information obtained from the patient visit checklist. This study was to determine the relationship of family support with chronic renal failure patient adherence to therapy in poly Haemodialysis Haemodialysis in hospital Blambangan, Banyuwangi in 2014.Research was obtained as many as 15 people (27.28%) patients with chronic renal failure aged 25-30 years, and 17 (30.9%) aged 41-50 years with a self-employed job and most of the heavy labor. Researchers hope that the hospitals can provide direction Blambangan Banyuwangi, in-depth knowledge about chronic kidney disease to patients and families of patients so that the family can fully support patient compliance in taking medication and undergoing therapy in a timely and appropriate.From the research, it was concluded that 9.1% of patients not adherent and 90.9% patient compliance with the treatment given by the hospitals Blambangan Banyuwangi.Keywords: Chronic Renal Failure, Hemodialysis, Family Support